Analysis of Kalam Khabar in Sūrah Al-Rūm/30: 41 and Its Implications for Environmental Damage - Andi Dian Wulandari; Andi Miswar; Mardan (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study departs from the issue of how the Qur’an conveys warnings about environmental destruction through linguistic structures containing rhetorical meanings. This research examines kalam khabar in sūrah al-Rūm/30:41 by emphasizing the form of khabar and the ecological messages contained within the verse. The study aims to reveal the function of kalam khabar in the verse while explaining its relevance to human awareness in preserving the environment. The method used is qualitative research with a library research approach through kalam khabar analysis and lexical analysis of sūrah al-Rūm/30:41. The findings show that the expression ظَهَرَ الْفَسَادُ فِي الْبَرِّ وَالْبَحْرِ belongs to the category of khabar ibtidā’i because it is delivered without emphatic elements (taukid), indicating that the information is directed toward an audience in a neutral condition (khālī al-dzihn). The verse also emphasizes that environmental destruction on land and sea is caused by human actions, thereby containing moral and ecological messages that encourage humanity to maintain the balance of nature. Thus, sūrah al-Rūm/30:41 not only conveys factual information about environmental destruction, but also presents a warning message that strengthens human responsibility toward nature. This study contributes to enriching Qur’anic linguistic studies, particularly regarding the analysis of kalam khabar in sūrah al-Rūm/30:41 and its relevance to environmental destruction issues.